Konsep dan Implementasi Mudharabah di Indonesia (Model, Aplikasi dan Tantangan dalam Lembaga Keuangan Syariah) - Taqwim, Andi Ahsan; Masse, Rahman Ambo; M, Misbahuddin (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Mudharabah is a cooperation agreement between two parties where the first party (shahibul maal) provides the entire (100℅) capital, while the other party becomes the manager. The profits of the venture are mudharabahly shared according to the agreement put forward in the contract, whereas when the loss is borne by the capital owner so long as the loss is not due to the negligence of the manager. If the loss was caused by the fraud or negligence of the manager, then the manager should be liable for the loss. Thus the basic concept of the mudharabah akad is present in this article and will be the center of analysis in its practice on Shariah financial institutions. The research method uses Literature study i.e. data collection method by understanding and studying the theories from various literature related to the study. The result of this discussion is that the akad mudharabah is widely used in financing and investment products because it complies with the Shariah principles of avoiding usury and emphasizing fairness and partnership. The Akad mudharabah provides an alternative solution within the Islamic economic system by foregrounding the values of transparency, trust, and shared responsibility.